P346 Single-centre experience of ustekinumab: Therapeutic drug monitoring in Crohn's disease patients. (15th January 2020) - Liefferinckx, C; Fassin, M; Thomas, D; Minsart, C; Cremer, A; Amininejad, L; Tafciu, V; Wambacq, V; Van Gossum, A; Franchimont, D
Abstract: Background: Therapeutic drug monitoring (TDM) is a diagnostic tool in the monitoring of anti-TNF therapies. Yet, the benefit for TDM of new biologics such as ustekinumab (USK) is still controversial in real-world experiences. Methods: This monocentric retrospective study aims to correlate USK trough levels (TLs) with clinical and endoscopic data. All patients have given written consent to the Biobank (B2011/005). Endoscopic disease was defined as quiescent in absence of endoscopic lesions, mild disease in presence of few superficial ulcerations, moderate in presence of several ulcers and severe in presence of numerous deep ulcers and/or inflammatory stenosis. 313 serum USK samples from 67 Crohn's disease patients were used to measure USK TL (USK ELISA, apDia) while 88 samples (at week 16, and before and after optimisation) were used to measure anti-drug antibody (ADA), using a drug-tolerant affinity capture elution anti-ustekinumab assay Results: Demographic and baseline data of our population are presented in Table 1. The median follow-up was 73 weeks (IQR 39–92). An optimisation due to loss of response was required in 44.8% of patients ( n = 30) after a median time of 38 weeks (IQR 24–55). To evaluate the drug efficacy, an endoscopy was performed in 61% of cases at a median time of 35 weeks (IQR 27–47). TLs were 5.2 µg/ml (IQR 2.1–8.8), 1.7 µg/ml (IQR 0.3–4.3) and 2.6 µg/ml (IQR 0.6–4.1) at week 8, 16 and 24, respectively. TLs at week 8 were correlated to the induction IV dose administrated ( r = 0.3, p = 0.03). At week 16, low TLs were associated with higher endoscopic activity in the follow-up ( p = 0.02), although this was not the case at week 8 ( p = 0.5) (Figure 1). Patients not requiring an optimisation had higher TLs in maintenance than patients requiring optimisation (2.45 µg/ml (IQR 1.3–4.4) vs. 1.15 µg/ml (IQR 0.1–2.24), p = 0.008). Obviously, optimisation significantly increased TLs (1.15 µg/ml (IQR 0.1–2.24) vs. 6.6 µg/ml (IQR 2.3–11.3), p < 0.001). ADA were undetectable in all the measured samples in maintenance. Conclusion: This real-world experience confirms a drug exposure-endoscopic response relationship. Week 16 seems to be an appropriate time point to monitor drug exposure. Earlier USK TLs, at week 8, appear less valuable to be monitored due to the influence of initial IV dose. The absence of immunogenicity suggests that it is not a key driver in the loss of response.